EMPYEMA THORACIS: MANAGEMENT OUTCOME - Ghaffar, Salma; Khan, Ishtiaq Ali; Asif, Sadia; Rahman, Zia ur (Journal of Ayub Medical College Abbottabad, 2010)
Background: Empyema thoracis results from postpneumonic effusion of bacterial origin or trauma. If untreated it may convert to fibro-purulent or an organising stage. Methods: This study was conducted at cardiothoracic unit of Ayub Teaching Hospital Abbottabad from Jan 2008 to Aug 2009. Patients with diagnosis of empyema thoracic were studied. Their clinical features and investigations were recorded on a proforma. Antibiotics alone, aspiration, chest intubation, rib resection or decortication were performed where required. Results: Out of 71 patients, males were 58 (81.69%) and females were 13 (18.3%). Majority of the patients (24, 33.8%), were below 20 years of age. Most of the patients (59, 83.09%), were from the poor socioeconomic class. Forty-one (57.76%) patients were smokers, 12 (16.9%) were diabetic, and 39 (54.92%) were hypertensive. Cough was the most common complain (62, 87.32%). Forty (56.33%) had more than 50% involvement of hemi thorax. In 44 (61.97%) cases, cause was tuberculosis. Fifty-one (71.83%) patients were treated with tube thoracostomy and 13 (18.3%) required decortication. Conclusion: Empyema thoracis commonly affects males. Apart from clinical assessment, x-ray chest is an important and simple investigation to detect empyema thoracic. Mostly tube drainage cures the diseases but in case of failure other options are also available. Keywords: Empyema thoracic, Chest intubation, rib resection, decortication